Faktor Faktor yang Berhubungan dengan Pemilihan Metode Kontrasepsi Jangka Panjang : Literature Review - Anik Purwanti; Ade Ifah Latifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The problem currently being experienced by the global community is the high number of maternal deaths and unwanted pregnancies, especially in developing countries. Female couples of childbearing age who do not use contraception will increase population problems in Indonesia. Currently, injection and pill contraceptive methods are still the public's favorite compared to long-term contraceptive methods. This is influenced by factors such as age, parity, education, employment, or other factors. The aim of this review is to identify factors that influence the choice of long-term contraceptive methods among couples of childbearing age in Indonesia. This research method uses a literature review. Articles are identified using databases from Google Scholar and PubMed. The research results showed that factors that influence the choice of long-term contraceptive methods include age >35 years, parity >2, higher education, working woman, good knowledge and attitude, positive husband support, and living in an urban area. Conclusion: Factors that influence the choice of contraceptive method in couples of childbearing age are age, parity, education, employment, knowledge, attitudes, husband's support, socio-economic status and place of residence.